Study of difference in cognitive functions after a single manic episode versus recurrent episodes in euthymic bipolar 1 patients - Ahuja, Bhavneet Kaur; Mishra, Vikash Chandra; Jain, Sanjay (International Journal of Research in Medical Sciences, 2018)
Background: Neurocognitive deficits have been substantially documented in patients with bipolar disorder in the euthymic state. The assessment of cognitive change from first episode mania is crucial in understanding whether cognitive deficits are progressive or already present from the first diagnostic episode of bipolar I disorder. The objective of the study is to assess and compare the cognitive function in bipolar I patients with one manic episode and recurrent episodes currently in remission. Methods: A cross sectional observational study consisting of 3 groups was carried on eighty cases each of bipolar 1 disorder patients in euthymic phase with one manic, more than 3 manic episodes and controls. These were subjected to the neuropsychological assessment and then compared. Results: The patients with recurrent episodes group shows poor performance upon digit span test, visuospatial memory test, verbal learning and memory test, color stroop test and trail making test than patients with single manic episode and healthy controls upon these cognitive tests. Conclusions: The present finding suggest that there is impairment in various cognitive domains like executive function, attention, memory even in bipolar patients after single manic episode.